2020
DOI: 10.3390/rs12091365
|View full text |Cite
|
Sign up to set email alerts
|

A Soil Erosion Indicator for Supporting Agricultural, Environmental and Climate Policies in the European Union

Abstract: Soil erosion is one of the eight threats in the Soil Thematic Strategy, the main policy instrument dedicated to soil protection in the European Union (EU). During the last decade, soil erosion indicators have been included in monitoring the performance of the Common Agricultural Policy (CAP) and the progress towards the Sustainable Development Goals (SDGs). This study comes five years after the assessment of soil loss by water erosion in the EU [Environmental science & policy 54, 438–447 (2015)], where a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 74 publications
2
65
0
1
Order By: Relevance
“…Citrus plantations also contribute to high erosion rates characterised such as was found in China (Liu et al 2012) and the Mediterranean belt (Cerdà and Jurgensen 2011). In the last three decades, a growth of the soil erosion measurements found that some other crops contribute to high erosion rates (Panagos et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Citrus plantations also contribute to high erosion rates characterised such as was found in China (Liu et al 2012) and the Mediterranean belt (Cerdà and Jurgensen 2011). In the last three decades, a growth of the soil erosion measurements found that some other crops contribute to high erosion rates (Panagos et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Also, models help assess the effectiveness/impact of soil and water conservation measures and agricultural, environmental, and climate policies. 118,119 Specific current challenges in the development and application of soil erosion models include (1 the non-linear relationships and thresholds between factors and processes; (2) the heterogeneity of model outputs obtained with different approaches at the same site; (3) the identification of stable areas; (4) the refinement of model predictions with accurate independent metrics of soil loss and deposition; (5) improved indicators of vegetation changes at a high temporal resolution using remote sensing; (6) upscaling model findings from the local scale to larger ones; and (7) integrating soil erosion processes with carbon sequestration, nutrient fluxes, diffuse contamination, and climate change scenarios.…”
Section: Runoff Soil Losses and Sediment Transport From The Pedon Tmentioning
confidence: 99%
“…The limitations of these strategies are site-specific and determined through the interaction of biochemical and physical factors as well as the social and institutional framework considered [1,20,21]. In Europe, an evidence of the current interest in this matter are the European Commission proposal of alignment of the Common Agricultural Policy (CAP)with the European Union's environmental, climate, and biodiversity protection commitments set in the European Green Deal [22][23][24] or the recent European Commission evaluation support study on the impact of CAP on sustainable soil management [25].…”
Section: Of 28mentioning
confidence: 99%